2008
DOI: 10.1007/s10147-007-0739-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of chemoradiotherapy for locally advanced pancreatic cancer in Japan

Abstract: Although the results of randomized controlled trials for locally advanced pancreatic cancer conducted between 1969 and 1988 demonstrated a survival advantage for concurrent radiotherapy and bolus 5-fluorouracil (FU) injection, the prognosis of patients with this disease remains very poor. In an attempt to improve patient outcome after chemoradiotherapy, various clinical trials for this disease have been conducted in Japan. These trials were designed to evaluate novel chemotherapy regimens combined with convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Even in patients with resectable disease, the long-term outcome remains unsatisfactory because of early recurrence after resection. (34) Therefore, alternative treatments are required to improve the prognosis of patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with resectable disease, the long-term outcome remains unsatisfactory because of early recurrence after resection. (34) Therefore, alternative treatments are required to improve the prognosis of patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant radiotherapy and chemotherapy is commonly used to treat locally unresectable pancreatic cancers [8]. S‐1 is expected to improve the outcomes of chemoradiotherapy for locally advanced pancreatic cancer because of its high palliative effectiveness, as well as its potent radiosensitizer activity . The preliminary results of a Japanese phase II study of S‐1 in patients with advanced pancreatic cancer demonstrated high safety and effectiveness [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…[1389] Radiation therapy alone or in combination with gemcitabine-based chemotherapy has a role in the treatment of locally advanced pancreatic cancer (eg, stage III), whereas its role in stage IV (metastatic) disease is palliative. [129091] Radiation therapy as pre- or post-operative treatment invokes controversy, and these are areas under study. Two groups of investigators proposed a new combination chemotherapeutic regimen, FOLFIRINOX (leucovorin, 5-fluorouracil, irinotecan, and oxaliplatin), and tested its effects on metastatic pancreatic cancer compared to gemcitabine.…”
Section: Potential Influence Of Gsk3β On Cancer Cell Susceptibility Tmentioning
confidence: 99%